Drug-Drug Interactions in Nosocomial Infections: An Updated Review for Clinicians - Sorina Hîncu; Miruna-Maria Apetroaei; Gabriela Ștefan; Anca Ionela Fâcă; Andreea Letiția Arsene; Beatrice Mahler; Doina Drăgănescu; Adriana-Elena Tăerel; Emilia Stancu; Lucian Hîncu; Andreea Zamfirescu; Denisa Ioana Udeanu (MDPI AG, 2024)
Prevention, assessment, and identification of drug-drug interactions (DDIs) represent a challenge for healthcare professionals, especially in nosocomial settings. This narrative review aims to provide a thorough assessment of the most clinically significant DDIs for antibiotics used in healthcare-associated infections. Complex poly-pharmaceutical regimens, targeting multiple pathogens or targeting one pathogen in the presence of another comorbidity, have an increased predisposition to result in life-threatening DDIs. Recognising, assessing, and limiting DDIs in nosocomial infections offers promising opportunities for improving health outcomes. The objective of this review is to provide clinicians with practical advice to prevent or mitigate DDIs, with the aim of increasing the safety and effectiveness of therapy. DDI management is of significant importance for individualising therapy according to the patient, disease status, and associated comorbidities.